On the Development of a Real Time Water Monitoring System - Zaharia Sandel (EDP Sciences, 2021)
The goal of the paper starts from the need for real-time monitoring of both running water and its affluents and urban sewerage systems with a role in discharging wastewater. The idea is to assess water quality and to determine the sources of pollutants resulting from human activity. The data quality will be obtained by purchasing them with a high resolution, both spatial and temporal, using multi-parametric sensors on a hardware platform of its own multisensory acquisition. The acquired data is stored in CLOUD or local server for storage, analysis and interpretation. There will be a software application based on artificial intelligence technologies that serves to identify and classify different polluted areas, locate pollution sources, predict their extinction, degree of pollution and help make decisions based on real-time detection. A web application will provide all the data collected in the field and it can be accessed on a common online platform. This allows researchers or employees of relevant agencies as well as city sewer system operators to validate the quality of data purchased from sensors and end users to be sure of their correctness.